PELATIHAN DESAIN GRAFIS MENGGUNAKAN APLIKASI CANVA DI SMK IBRAHIMY 1 SUKOREJO SITUBONDO - Lu’luul Maulidya Nova; Siti Nabilatul Hoiroh; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
This community service activity aimed to develop the graphic design skills of the female students at SMK Ibrahimy 1 Sukorejo through training on the use of the Canva application. The training was conducted to motivate students to utilize Canva optimally. The method employed was a descriptive qualitative approach consisting of three main stages: preparation, implementation, and evaluation. The training was carried out virtually and involved 49 participants, covering lecture sessions, Q&A discussions, and practical poster-making exercises. The evaluation results showed that most participants felt satisfied and benefited from the training. In addition to enhancing graphic design skills, this activity was also intended to foster creativity, boost self-confidence, and cultivate entrepreneurial potential among students in the creative industry sector. The average satisfaction level among participants was 90.4%. Therefore, this training proved effective as a means of empowering students to face the challenges of a digitally driven job market.